Managing acute agitation and aggression in the world of drug shortages - Jennifer Miller, PharmD, BCPP (American Association of Psychiatric Pharmacists, 2021)
Acute agitation and aggression create safety risks for both patients and staff, often leading to psychiatric emergencies. Quick and appropriate treatment is necessary to achieve safe and effective outcomes. Unfortunately, there are several factors that hinder timely interventions, such as medication shortages and delay in staff preparedness. Ultimately, the goal of managing acute agitation and aggression in the clinical setting is to de-escalate the situation and prevent harm to patients and staff. This article will explore useful interventions in realizing treatment goals for the management of agitation and aggression in adults while navigating limitations faced in practice.